Lemmel’s Syndrome in an Elderly Patient with Recurrent Biliary Obstruction: A Detailed Case Report - Chaurasia, Shivaom; Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2025)
Lemmel’s syndrome, an uncommon cause of obstructive jaundice due to a periampullary diverticulum, can pose significant diagnostic and therapeutic challenges. This report describes an 80-year-old male who presented with right upper quadrant pain and jaundice. Initial cross-sectional imaging, including contrast-enhanced Computed Tomography and Magnetic Resonance Cholangiopancreatography, demonstrated marked dilation of the bile ducts and distal common bile duct narrowing without any discernible intraluminal lesion. A large diverticulum near the ampulla of Vater was also identified, and tumor markers were negative, which led to us suspecting Lemmel’s syndrome. Endoscopic retrograde cholangiopancreatography with sphincterotomy yielded temporary symptom relief and normalization of liver function tests. However, the patient experienced recurrent postprandial pain and abnormal liver enzymes shortly thereafter, both of which resolved spontaneously with conservative management. These findings confirmed the diagnosis of Lemmel’s syndrome, underscoring the importance of a high index of clinical suspicion, advanced imaging modalities, and a multidisciplinary approach in elderly patients with anatomical variations. This case highlights the need for a thorough investigation of refractory biliary obstruction and emphasizes the role of careful follow-up to optimize patient outcomes.